Potential of integrating entomopathogenic and endophytic fungal based biopesticides for sustainable management of the South American tomato pinworm, Phthorimaea absoluta (Meyrick) (Lepidoptera: Gelechiidae) - Yusuf, Abdullahi Ahmed (University of Pretoria, 2023)
Thesis (PhD (Entomology))--University of Pretoria, 2023.